2020
DOI: 10.4060/cb1271en
|View full text |Cite
|
Sign up to set email alerts
|

The economics of pastoralism in Argentina, Chad and Mongolia

Abstract: The designations employed and the presentation of material in this information product do not imply the expression of any opinion whatsoever on the part of the Food and Agriculture Organization of the United Nations (FAO) or Centre de Coopération Internationale en Recherche Agronomique pour le Développement (CIRAD) concerning the legal or development status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. The mention of specific compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Little information is available to assess the economic benefits of silvopastoralism. The use of forest resources as source of fodder and additional revenue is common among pastoralists, but there is scarce data available on their actual value (Wane et al, 2020). However, the research cited in this section represents sound evidence that silvopastoralism can perform better than single-crop or monospecific livestock farming systems under similar conditions.…”
Section: Is Silvopastoralism Economically Profitable?mentioning
confidence: 94%
See 1 more Smart Citation
“…Little information is available to assess the economic benefits of silvopastoralism. The use of forest resources as source of fodder and additional revenue is common among pastoralists, but there is scarce data available on their actual value (Wane et al, 2020). However, the research cited in this section represents sound evidence that silvopastoralism can perform better than single-crop or monospecific livestock farming systems under similar conditions.…”
Section: Is Silvopastoralism Economically Profitable?mentioning
confidence: 94%
“…Silvopastoralism promotes the diversified production income of forests, trees and livestock, mainly in less productive seasons, and contributes to an improvement in the quality and variety of local diets by adding TASF. An FAO study in Argentina, Chad and Mongolia (Wane et al, 2020) showed the multifunctional contribution of livestock grazing in woods and grasslands to socioeconomic dimensions, especially in remote areas. Animals, milk, hides, and so on, represent between 38 and 74 percent of monetary income and self-consumption represents between 8 and 37 percent of additional income.…”
Section: Chapter 3: a Framework For Applying The Silvopastoral Approa...mentioning
confidence: 99%
“…Today Latin America is one of the most controversial regions, as it has both regional leaders, such as Brazil and the countries with rather weak economies, for instance, Bolivia or Paraguay, while Colombia has a unique economic model, which is tightly connected with tourism, and is supported by illegal drug exports (Loayza et al 2019;Wainwright 2016). The overall performance of the economies of the continent can be characterized as unstable and hence the sustainability issues are the key topic for the future development of the continent.…”
Section: Introductionmentioning
confidence: 99%